2012
DOI: 10.1177/1440783312458226
|View full text |Cite
|
Sign up to set email alerts
|

De-intellectualizing American sociology

Abstract: Sociology once debated 'the social' and did so with a public readership. Even as late as the Second World War, sociologists commanded a wide public on questions about the nature of society, altruism and the direction of social evolution. As a result of several waves of professionalization, however, these issues have vanished from academic sociology and from the public writings of sociologists. From the 1960s onwards sociologists instead wrote for the public by supporting social movements. Discussion within soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…The findings support Greenwood and Levin [40], Levin and Greenwood [41], and Turner's [7] critique of current social sciences, as well as Turner's ( [8] p. 479) call for science studies' colleagues "to ask the politically uncomfortable questions we find so difficult", and Wood's [121] insisting on reflecting upon the terms by which research is framed by funders. They add proofs of the perniciousness of conformist survey research that without the sociological reflexivity proposed by Bourdieu [64] advances academic careers by submitting to power-holders' wish to tell powerless subjects whatever serves the formers' dominance.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 65%
See 2 more Smart Citations
“…The findings support Greenwood and Levin [40], Levin and Greenwood [41], and Turner's [7] critique of current social sciences, as well as Turner's ( [8] p. 479) call for science studies' colleagues "to ask the politically uncomfortable questions we find so difficult", and Wood's [121] insisting on reflecting upon the terms by which research is framed by funders. They add proofs of the perniciousness of conformist survey research that without the sociological reflexivity proposed by Bourdieu [64] advances academic careers by submitting to power-holders' wish to tell powerless subjects whatever serves the formers' dominance.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 65%
“…Functionalists managed to retain the credibility of their findings and their academic prestige by never admitting mistakes, helped by international research cooperation 7 and publishing in major international outlets whose reviewers approved erroneous works lacking "the profound intuitions gained from personal familiarity with the field" ([60] p. 3) and/or due to functionalism. Functionalists were aware of the mass exit from kibbutzim (e.g., [122] p. 163) and saw talented innovative leavers succeeding in every domain of Israeli society and abroad [123] thus testifying to a brain-drain due to conservative oligarchic rule, but they ignored it, studying neither leavers nor exit rates, since this would have exposed the negative effects of oligarchic rule, contradicting their rosecolored descriptions.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the specific methodological debates occurring during this period of expanded strategic funding also had an implicit political content. Even among scholars that were personally committed to left politics, these methodological debates often favored empirical, rather than theoretical or “ideological” (i.e., Marxist) approaches to social scientific research (Turner, ). Many scholars thus actively reinforced the discursive weight of “science” as a counter to “ideology,” including Paul Lazarsfeld and his colleagues at Columbia.…”
Section: The Legacy Of Voter Studies: Removing the ‘Social’ From Polimentioning
confidence: 99%
“…While this reconstruction leaves out a significant amount of his work dedicated to advancing quantitative research, I argue that the qualitative approach Lazarsfeld suggested for political research is particularly important because it ran counter to behavioralist and rational choice approaches that facilitated the eventual dominance of formal quantitative models in postwar research on democracy. At the same time, Lazarsfeld also played his role in reducing the theoretical and methodological diversity of the upper tiers of American sociology (see Turner, ), which led to personal and professional conflicts that still echo within the discipline. Even so, in much of Lazarsfeld's work it is clear that he takes a more expansive view of “methodology” and “empirical research” than he often receives credit for (Boudon, ).…”
mentioning
confidence: 99%